Kinetic energy spectra characteristics of two convection‐permitting limited‐area models AROME and Meso‐NH. (16th November 2012) - Ricard, D.; Lac, C.; Riette, S.; Legrand, R.; Mary, A.
Abstract Kinetic energy (KE) spectra are applied to evaluate two convection‐permitting models: the AROME numerical weather prediction operational model and the Meso‐NH research model, that share the same physics and differ only in the dynamics (semi‐Lagrangian semi‐implicit versus Eulerian explicit schemes). A first analysis of AROME spectra for winter and summer seasons shows that the model‐derived spectra match the observational spectra well, including the transition between k−3 and k−5/3 regimes. The vertical distribution of the spectra is coherent with previous observational and numerical studies and the diurnal cycle has a strong impact on the amount of KE in the mesoscale during summer. A comparative analysis of KE spectra for both models is then performed on a real case of individual convective cells that developed over plains, during the afternoon of 11 April 2007, characterized by a strong cold air outflow in the low levels. AROME spectra are characterized by a coarser effective resolution than Meso‐NH, even without explicit diffusion, revealing the impact of the implicit diffusion of the semi‐implicit semi‐Lagrangian scheme used in AROME. For large time steps, the damping increases and can be attributed preferentially to the SI part of the SISL (semi‐implicit semi‐Lagrangian) formulation. Adiabatic runs show that the transition to a shallow mesoscale regime is still apparent even if the mesoscale KE variance strongly depends on the presence of the physical processes. Effective resolution of Meso‐NH remains around 4–6Δx for horizontal grid spacings between 2.5 km and 250 m. The effects of subgrid mixing schemes are also investigated with Meso‐NH at 500 m horizontal grid spacing in the grey zone for turbulence, illustrating the difficulty in finding a good equilibrium between resolved and subgrid mixing at this scale.